Progenitor Cell Therapy for Neurological Injury - Charles, S.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
There are currently no reparative therapies for severe neurological injury, including brain injury, spinal cord injury and stroke. Actually, most treatments are designed simply to limit secondary damage. However, pre-clinical data supports the idea that exogenous stem and progenitor cells have the potential to promote a reparative response to severe neurological injuries. Progenitor Cell Therapy for Neurological Injury is a compilation of seminal essays that explore many unique aspects of neurological injury, focusing on the critical translational issues of cell delivery. Specifically, it discusses routes of administration, types of progenitor cells (alone and/or in combinations), timing of delivery and adjuncts to promote cell engraftment, survival and effectiveness. In addition, many chapters address measuring the effects of transplanted cells and cell tracking. The paradigms of how cell-based therapeutics affect neurological injury is changing rapidly. The developments in this field may ultimately offer realistic hope for improvement in patients with severe injuries. This book is a vital key toward unlocking those future treatments.
Preface -- Chapter 1. Basics of Stem and Progenitor Cells -- Chapter 2. Progenitor Cell Tissue Engineering: Scaffold Design and Fabrication -- Chapter 3. Stem Cell Delivery Methods and Routes -- Chapter 4. Neural Stem Cells-Endogenous Repair of Neurological Injury -- Chapter 5. Traumatic Brain Injury: Pathophysiology and Models -- Chapter 6. Traumatic Brain Injury: Relationship of Clinical Injury to Progenitor Cell Therapeutics -- Chapter 7. Cell-Based Therapy for Stroke -- Chapter 8. Spinal Cord Injury: Pathophysiology and Progenitor Cell Therapy -- Chapter 9. Current Status of Clinical Trials using Progenitor Cells for Neurological Injury.
Keywords: Life sciences; Stem cells; Life Sciences; Stem Cells